Polymer beads
By using an anion exchange composition containing polymer beads and tin (II) oxide contact with water, the problem of difficulty in removing hexavalent chromium in the prior art is solved, and an efficient water purification effect is achieved.
Patent Information
- Application Number
- CN201880077903.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-01-11
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2039-01-11
AI Technical Summary
The prior art is difficult to effectively remove hexavalent chromium (Cr(VI) from water, especially in industrial processes requiring efficient removal.
Using an anion exchange composition comprising polymer beads with covalently bound amine groups and tin (II) oxide, chromium is achieved by contacting water containing dissolved chromium (VI) with the composition ( VI) removal.
This method significantly improves the removal efficiency of hexavalent chromium, can effectively treat water containing chromium (VI), reduces the residue of pollutants, and improves the purification effect of water.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
[0001] Hexavalent chromium, also known as chromium (VI), is widely used in various industrial processes. Hexavalent chromium is sometimes present in water as an undesirable contaminant. Methods for removing hexavalent chromium from water are desirable.
[0002] US 7,708,892 describes the use of ion exchangers doped with metals. According to US 7,708,892, the metal used for doping can be any of a variety of metals. According to US 7,708,892, metal-doped ion exchangers can be used to remove a variety of dissolved contaminants from water, including contaminants containing both oxygen atoms and metal atoms, wherein the metal atoms can be selected from a variety of metals. It is desirable to provide an ion exchange composition that is particularly effective in removing hexavalent chromium from water.
[0003] The following is a statement of the invention.
[0004] A first aspect of the present invention is an anion exchange composition comprising
[0005] (a) polymer beads having covalently bonded amine groups, and
[0006] (b) Tin(II) oxide.
[0007] A second aspect of the invention is a method of treating water comprising contacting water containing dissolved chromium (VI) with an anion exchange composition comprising:
[0008] (a) polymer beads having covalently bonded amine groups, and
[0009] (b) Tin(II) oxide.
[0010] The following is a detailed description of the present invention.
[0011] As used herein, the following terms have the designated definitions unless the context clearly dictates otherwise.
[0012] As used herein, "polymer" is a relatively large molecule composed of the reaction product of smaller chemical repeating units. Polymers can have a structure that is linear, branched, star-shaped, cyclic, hyperbranched, cross-linked, or a combination thereof; polymers can have a single type of repeating unit (a "homopolymer") or they can have more than one type of repeating unit (a "copolymer"). Copolymers can have various types of repeating units arranged randomly, sequentially, in blocks, in other arrangements, or any mixture or combination thereof.
[0013] Molecules that can react with each other to form repeating units of a polymer are referred to herein as "monomers." The repeating units so formed are referred to herein as "polymerized units" of the monomer.
[0014] Vinyl monomers have the structure Where R 1 , R 2 , R 3 , and R 4 Each is independently hydrogen, a halogen, an aliphatic group (such as, for example, an alkyl group), a substituted aliphatic group, an aryl group, a substituted aryl group, another substituted or unsubstituted organic group, or any combination thereof. Vinyl monomers are capable of free radical polymerization to form polymers. Some vinyl monomers have R 1 , R 2 , R 3 and R 4 Such vinyl monomers are referred to herein as multifunctional vinyl monomers. Vinyl monomers having exactly one polymerizable carbon-carbon double bond are referred to herein as monofunctional vinyl monomers.
[0015] Styrene monomers are vinyl monomers such as: 1 and R 2 Each is hydrogen, R 3 is hydrogen or alkyl and -R 4 With the following structure
[0016]
[0017] Where R 5 , R 6 , R 7 , R 8 , and R 9 Each is independently hydrogen, a halogen, an aliphatic group (such as, for example, an alkyl group or a vinyl group), a substituted aliphatic group, an aryl group, a substituted aryl group, another substituted or unsubstituted organic group, or any combination thereof.
[0018] The reaction between monomers to form one or more polymers is referred to herein as a polymerization process.
[0019] A polymer is considered herein to contain polymerized units of the monomers used to prepare the polymer, even if, after polymerization, some or all of these polymerized units are modified by the addition of one or more functional groups. For example, a copolymer prepared from styrene and DVB in a weight ratio of styrene:DVB of 90:10 is considered to have 90% by weight polymerized units of styrene. If the copolymer is subsequently modified by reaction with sulfuric acid to replace some of the hydrogen atoms on the aromatic rings with sulfonic acid groups, the resulting functionalized polymer is still considered to have 90% by weight polymerized units of styrene.
[0020] The macroporous polymer beads have a porous structure with an average pore size of 20 nm or more. The pore size is measured using the Brunauer-Emmett-Teller (BET) method with nitrogen. Macroporous polymer beads are typically prepared by incorporating a porogen into a monomer droplet. The porogen is soluble in the monomer, but the polymer is not soluble in the porogen, so as the polymer is formed, phase-separated domains of the porogen are retained. After polymerization, the porogen is removed by evaporation or by washing with a solvent. The porous structure of the polymer beads is the empty space left behind when the porogen is removed from its phase-separated domains.
[0021] The preparation of gel-type polymer beads does not use porogens. The pores in the gel-type polymer beads are the free volume between atoms in the entangled, possibly cross-linked polymer chains of the polymer beads. The pores in the gel-type polymer beads are less than 20 nm. In some cases, the pores in the gel-type resin are too small to be detected using the BET method.
[0022] As used herein, ion exchange is a process in which a solution is contacted with an ion exchange resin. Prior to contact with the solution, the ion exchange resin has functional groups of a certain charge and has ions of the opposite charge associated with the functional groups. When the solution is contacted with the ion exchange resin, some of the ions in the solution attach to the ion exchange resin through ion exchange sites of the same charge associated with the functional groups on the ion exchange resin.
[0023] Polymer beads are particles containing 90% by weight or more of an organic polymer based on the weight of the particle. The polymer beads are spherical or nearly spherical. The polymer beads are characterized by their radius. If the beads are not spherical, the radius of the bead is taken herein as the radius of a "reference sphere", which is an imaginary sphere having the same volume as the bead.
[0024] As used herein, "ambient temperature" is synonymous with "room temperature" and is about 23°C.
[0025] Aggregates of particles can be characterized by their volume mean diameter.
[0026] Ratios are characterized herein as follows. For example, if a ratio is considered to be 5:1 or higher, it means that the ratio can be 5:1 or 6:1 or 100:1, but not 4:1. To state this characterization in a general way, if a ratio is considered to be X:1 or higher, then the ratio is Y:1, where Y is greater than or equal to X. Similarly, for example, if a ratio is considered to be 2:1 or lower, it means that the ratio can be 2:1, or 1:1, or 0.001:1, but not 3:1. To state this characterization in a general way, if a ratio is considered to be Z:1 or lower, then the ratio is W:1, where W is less than or equal to Z.
[0027] The anion exchange composition of the present invention contains an aggregate of polymer beads. The polymer beads contain a polymer. The polymer beads are particles that are solid at 25°C and contain the polymer in an amount of 90% by weight or more based on the weight of the polymer particles; more preferably 95% by weight or more.
[0028] The anion exchange composition of the present invention also contains tin (II) oxide. Preferably, the sum of the weight of the polymer beads and tin (II) oxide is 90% or more, more preferably 95% or more, and more preferably 99% or more, based on the total weight of the anion exchange composition.
[0029] The polymer beads may be macroporous beads or gel beads. Macroporous beads are preferred.
[0030] Preferred polymers in the polymer particles are polymers formed by free radical polymerization of vinyl monomers.
[0031] Preferred vinyl monomers are styrene monomers, acrylic monomers and mixtures thereof. Preferably, all monomers used are selected from styrene monomers, acrylic monomers and mixtures thereof; more preferably selected from styrene monomers. More preferably, all monomers used are selected from styrene monomers. The vinyl monomers preferably include one or more monofunctional vinyl monomers. Preferred monofunctional vinyl monomers are acrylic and styrene monofunctional monomers; more preferably monofunctional styrene monomers; more preferably styrene. The vinyl monomers preferably include one or more multifunctional vinyl monomers. Preferred multifunctional vinyl monomers are multifunctional styrene monomers; more preferably divinylbenzene.
[0032] Preferred polymers in the polymer particles contain polymerized units of styrene monomers in an amount of 5 wt % or more based on the weight of the polymer; more preferably 25 wt % or more; more preferably 50 wt % or more; more preferably 75 wt % or more; more preferably 95 wt % or more.
[0033] Preferred polymers have polymerized units of multifunctional vinyl monomers in an amount of 1 wt% or more based on the weight of the polymer; more preferably 1.5 wt% or more; more preferably 2 wt% or more. Preferred polymers have polymerized units of multifunctional vinyl monomers in an amount of 25 wt% or less based on the weight of the polymer; more preferably 20 wt% or less; more preferably 15 wt% or less; more preferably 11 wt% or less; more preferably 6 wt% or less.
[0034] Preferred polymers have polymerized units of monofunctional vinyl monomers in an amount of 99% by weight or less based on the weight of the polymer; more preferably 98.5% by weight or less; more preferably 98% by weight or less; more preferably 98.5% by weight or less. Preferred polymers have polymerized units of monofunctional vinyl monomers in an amount of 75% by weight or more based on the weight of the polymer; more preferably 80% by weight or more; more preferably 85% by weight or more; more preferably 89% by weight or more; more preferably 94% by weight or more.
[0035] Preferably, after copolymerization of the monomers, the polymer is subjected to a conversion process to produce an anion exchange resin. Anion exchange resins are classified into the following categories. Weak base anion exchange resins have primary, secondary or tertiary pendant amino groups. Strong base anion exchange resins have pendant quaternary ammonium groups. When any of these pendant functional groups have been attached to the polymer beads, the beads are referred to as "functionalized resins".
[0036] Typically, when an anion exchange resin is prepared from polymer beads (such as cross-linked polystyrene beads), the beads are advantageously haloalkylated, preferably halomethylated, most preferably chloromethylated, and the ion-active exchange groups are subsequently attached to the haloalkylated copolymer. Typically, the haloalkylation reaction comprises swelling the cross-linked addition copolymer with a haloalkylating agent, and then reacting the copolymer with the haloalkylating agent in the presence of a Friedel-Crafts catalyst. Typically, weak base anion exchange resins are prepared by reacting haloalkylated copolymers with ammonia, primary amines or secondary amines. Typically, strong base anion exchange resins are prepared by reacting haloalkylated copolymers with tertiary amines.
[0037] The collection of polymer beads of the present invention also contains tin (II) oxide. Tin (II) oxide can be introduced into the collection of polymer beads by any method. A preferred method is to provide anion exchange resin polymer beads and contact the beads with an aqueous solution containing dissolved tin (II) ions, such as an aqueous solution of tin (II) chloride. Preferably, after removing the beads from the solution containing tin (II) ions, the beads are then contacted with an aqueous solution having a pH above 8, such as an aqueous sodium hydroxide solution. After removing the beads from the solution having a pH above 8, the beads are preferably washed with water.
[0038] Preferably, the volume average diameter of the aggregate of polymer beads is 200 microns or more; more preferably 400 microns or more, more preferably 600 microns or more. Preferably, the volume average diameter of the aggregate of polymer beads is 1,500 microns or less; more preferably 1,000 microns or less.
[0039] In addition to the polymer, the collection of polymer beads normally also contains water. It is expected that the water is adsorbed into the functionalized polymer beads. The amount of water is assessed by removing liquid water (if any is in contact with the polymer beads) and then equilibrating the beads with air at 100% relative humidity at 23°C. The amount of water in the beads is preferably 30% by weight or more, based on the total weight of the functionalized polymer beads (including both the beads and the adsorbed water); more preferably 50% by weight or more; more preferably 60% by weight or more; more preferably 70% by weight or more. The amount of water in the beads is preferably 90% by weight or less, based on the total weight of the collection of functionalized polymer beads.
[0040] The amount of tin in the collection of polymer beads is characterized as the weight of elemental tin relative to the total weight of the anion exchange composition. Preferably, the amount of tin is 0.5% or more; more preferably 1% or more; more preferably 2% or more; more preferably 3% or more. Preferably, the amount of tin is 25% or less; more preferably 20% or less; more preferably 15% or less; more preferably 10% or less.
[0041] Preferably, most or all of the tin present in the aggregate of polymer beads is in the form of tin(II) oxide. Preferably, the amount of tin present in the form of tin(II) oxide, as a molar percentage of the total tin present, is 90% or more; more preferably 95% or more; more preferably 99% or more.
[0042] Preferably, most or all of the tin(II) oxide is present inside the polymer beads or at the surface of the polymer beads or a mixture of the two, and is not present in the gaps between the polymer beads. Preferably, based on the total weight of the tin(II) oxide, 90% by weight or more of the tin(II) oxide is located inside the polymer beads. Preferably, based on the total weight of the tin(II) oxide, 80% by weight or more of the tin(II) oxide is in the form of particles having a diameter of less than 10 microns; more preferably 5 microns or less; more preferably 2 microns or less; more preferably 1 micron or less.
[0043] It is useful to characterize a less preferred form of tin(II) oxide, herein labeled "external" tin(II) oxide, as tin(II) oxide in the form of particles of any size of 10 microns or greater located in the interstices between the polymer beads, whether or not such tin(II) oxide particles are in contact with the surface of one or more polymer beads. Preferably, the amount of external tin(II) oxide as a mole percent of the total tin(II) oxide is 10% or less; more preferably 5% or less; more preferably 2% or less; more preferably 1% or less; more preferably zero.
[0044] Preferably, the polymer beads contain little or no metal other than tin(II). Preferably, the ratio of the total weight of all metals as elemental metals to the weight of elemental tin(II) is 0.5:1 or less; more preferably 0.2:1 or less; more preferably 0.1:1 or less; more preferably 0.05:1 or less; more preferably 0.02:1 or less; more preferably 0.01:1 or less.
[0045] A preferred use of the polymer beads of the present invention is to treat water containing dissolved chromium (VI) ions (hereinafter "pre-treatment" water). The chromium (VI) ions may be present as part of any molecule, ion or complex, as long as the chromium is in the (VI) oxidation state and as long as the molecule, ion or complex is dissolved in the pre-treatment water. Preferred are anions containing chromium (VI). Examples of anions containing chromium (VI) are HCrO4 - 、CrO4 2- , and Cr2O7 2- . Preferably, the water before treatment contains 0.01 ppm or more of chromium (VI) as atomic chromium, based on the total weight of the water before treatment; more preferably 0.02 ppm or more; more preferably 0.05 ppm or more. Preferably, the water before treatment contains 100 ppm or less of chromium (VI) as atomic chromium, based on the total weight of the water before treatment; more preferably 50 ppm or less; more preferably 25 ppm or less; more preferably 10 ppm or less; more preferably 5 ppm or less; more preferably 2 ppm or less; more preferably 1 ppm or less.
[0046] The water before treatment optionally contains one or more additional dissolved compounds. Preferred additional dissolved compounds are inorganic salts. Preferably, the total amount of all dissolved compounds is 1 wt % or less based on the total weight of the water (including dissolved compounds); more preferably 0.3 wt % or less; more preferably 0.1 wt % or less.
[0047] Preferably, the pre-treated water is treated by contacting the pre-treated water with the polymer beads of the present invention. The contacting can be performed by any method, including, for example, batch methods and column methods.
[0048] In a batch process, the water and polymer beads prior to treatment are placed in a container and optionally mechanically agitated. Preferably, the water (now referred to herein as "treated water") is then separated from the polymer beads, for example by a process including decantation or filtration or a combination thereof. In a batch process, it is useful to define the ratio "R1" as the ratio of the weight of the polymer beads in grams (measured as wet beads in the absence of bulk water) to the total weight of atomic chromium (VI) in grams in the batch.
[0049] In the column method, an assembly of polymer beads is placed in a container that captures the polymer beads in place, the container having an inlet for water to enter the container and an outlet for water to leave the container, the inlet allowing water to flow through the container while in close contact with the polymer beads. Water before treatment is introduced through the inlet, forced through the column by gravity or a pump or a combination thereof, and then leaves the column through the outlet. After leaving the column, the water is labeled "treated water" herein.
[0050] In the column method, the ratio R1 is characterized as follows. Using beads that are moist but without the presence of bulk water, the weight of the aggregate of polymer beads is measured in grams. Pre-treatment water is passed through the column and the flow is then stopped. The weight of chromium (VI) is considered to be the total weight, in grams, of all atomic chromium (VI) in all pre-treatment water entering the column. The ratio R1 is then the ratio of the weight of the aggregate of polymer beads to the weight of chromium (VI).
[0051] Regardless of whether the method used is a batch method or a column method, R1 is preferably 300:1 or greater; more preferably 450:1 or greater; more preferably 900:1 or greater. Preferably, R1 is 10,000:1 or less.
[0052] The following are examples of the present invention.
[0053] The following properties are used to characterize an aggregate of polymer beads. "VMD" is the volume-based mean diameter of the particles, in micrometers (μm). "EQ-water" is the amount of water found in an aggregate of polymer beads after exposing the beads to liquid water, removing excess liquid water and allowing the beads to equilibrate with air at 100% relative humidity at 23°C; the beads are then weighed, dried, and weighed again; and the difference in weight is "EQ-water", expressed as the weight of water as a percentage of the initial total weight of the beads (including water).
[0054] The following abbreviations are used in the following examples.
[0055] DI = Deionized
[0056] ND = Not Detected - the detection limit for chromium is 0.05 μg / g
[0057] Sty / DVB = copolymer of styrene, divinylbenzene and ethylvinylbenzene
[0058] polycond=condensation polymer
[0059] Four resins were used. Before the introduction of tin(II) oxide, these four resins had the following properties:
[0060]
[0061] (1) Comparison
[0062] (2) Quaternary ammonium
[0063] (3) Large pores
[0064] The following tin stock solutions were used:
[0065] Tin(II) stock solution: 35g tin(II) chloride / 1000mL DI water
[0066] Tin(IV) stock solution: 45g Tin(IV) chloride / 1000mL Di water
[0067] The following feed solutions (i.e., "water before treatment") were prepared:
[0068] <![CDATA[ CrO3 ]]> <![CDATA[ NaCl ]]> <![CDATA[ Na2SO4 ]]> <![CDATA[ CaCl2 ]]> <![CDATA[ MgCl2 ]]> <![CDATA[ DI water ]]> Feed A 0.014g 1.05g 0.35g -- -- 7L Feed B 0.10g 1.5g 0.5g -- -- 10L Feed C 0.102g 1.5g 0.493g 0.749g 0.745g 10L Feed D 0.250g 1.5g 0.503 0.404 0.352 10L
[0069] Example 1: Loading Tin onto Resin
[0070] Loading tin onto the resin was performed as follows. The resin was centrifuged to remove the bulk water to obtain a "wet" resin. 1 L of resin was mixed with 2 L of the stock solution. The mixture was stirred for 4 hours and then decanted. A small sample of the resin was taken for analysis. The remaining resin was mixed with 1.5 L of a 1.0 N NaOH aqueous solution. The mixture was stirred for about 14 hours and then decanted. The resin was washed thoroughly with DI water.
[0071] The tin content of the resin was measured using inductively coupled plasma (ICP) emission spectroscopy. The detection limit of tin was 5 ppm by weight. The resin samples were tested in three stages: before exposure to the stock solution ("Cl" or "free base" stage), immediately after exposure to the stock solution ("SnCl2" or "SnCl4" stage), and after decantation from the NaOH solution ("NaOH" stage). The amount of tin is reported as the weight of elemental tin as a percentage of the total weight of the resin (i.e., the total weight of the aggregate of polymer beads). The results are as follows:
[0072] <![CDATA[ Instance Type ]]> <![CDATA[ Resin ]]> <![CDATA[ Stock solution ]]> <![CDATA[ stage ]]> <![CDATA[ Tin wt% ]]> preparation SBA-MP none Cl ND preparation SBA-MP Sn(II) <![CDATA[SnCl2]]> 0.3 Work SBA-MP Sn(II) NaOH 4.4 Contrasting SBA-MP Sn(IV) <![CDATA[SnCl4]]> 4.5 Contrasting SBA-MP Sn(IV) NaOH 5.6 Contrasting SAC-Gel-C none Free base ND Contrasting SAC-Gel-C Sn(II) <![CDATA[SnCl2]]> 4.3 Contrasting SAC-Gel-C Sn(II) NaOH 2.9
[0073] In the above table, the material made from SBA-MP (treated with Sn(II) stock solution and also treated with NaOH solution) is the only material of the working example of the composition of the present invention. The other materials shown are prepared, represent intermediate steps in the way to make the working examples, or are comparative examples. Materials using Sn(IV) or using SAC resin are not within the scope of the present invention.
[0074] The SAC resin absorbed less tin from the stock solution than the SBA resin. In addition, the amount of tin decreased in the SAC resin due to the NaOH treatment. It is believed that the SAC-Gel-C resin at its final stage has much less tin (II) oxide than the SBA-MP resin at its final stage.
[0075] Three resins were studied by visual observation and optical microscopy: (1) SBA-MP with tin (II) oxide after the NaOH stage; (2) SBA-MP with tin (IV) oxide after the NaOH stage, and (3) SBA-MP without tin treatment. For each resin, 5 g of the corresponding resin was placed in a 60 mL bottle containing 50 mL of chromium oxide (CrO3) solution with a concentration of 0.25 g / 50 mL, and the pH was adjusted to 7.2 using NaOH. Each resin / CrO3 solution was placed on a shaker and stirred at room temperature (about 23°C) for 72 hours. The resin was allowed to settle, the excess liquid was poured into a waste container, and the resin was visually inspected. Neither the resin / Sn(II) hybrid nor the resin control showed signs of metal precipitation outside the resin beads, while the resin / Sn(IV) hybrid showed obvious dark granular insoluble precipitation at the bottom of the resin. The three resins were also examined by optical microscopy. In the Wuxi sample and the tin (II) oxide sample, no particles other than the polymer beads were observed. In the tin (IV) oxide sample, many external particles other than the polymer beads were seen. These external particles were identified as tin (IV) oxide, and the external particles covered about 80% of the field of view. It is believed that the observation and microscopic images of the resin show that tin (II) oxide is formed inside the polymer beads or directly on the surface of the beads, while tin (IV) oxide has a greater tendency to form particles in the gaps between the polymer beads.
[0076] Example 2: Treating water
[0077] In each experiment, a certain amount of resin (see below) was placed in a 1000 mL conical flask containing 1000 mL of feed solution. The mixture was stirred continuously and the chromium content in the water was tested after 3 and 8 days. Chromium was studied using ICP and reported in units of micrograms of chromium per gram of water (μg / g). The detection limit was 0.05 μg / g. The results are as follows:
[0078] 0.75g resin / feed A
[0079]
[0080] The working example of the present invention in the above table is SBA-MP / Sn(II) / NaOH. This example has the best chromium removal performance, especially at day 8.
[0081] Resin SBA-MP / Feed B
[0082]
[0083] In the above table, the working examples of the present invention are three samples with Sn(II). These samples can remove chromium very well.
[0084] Example 3: Further loading of resin
[0085] The resin was loaded with tin as follows. The resin was loaded as in Example 1 above, except that 1 L of resin was mixed with 1 L of the stock solution in each sample. The equilibrium water content and tin content were measured by the methods described above, and the results are as follows.
[0086] <![CDATA[ Instance Type ]]> <![CDATA[ Resin ]]> <![CDATA[ Stock solution ]]> <![CDATA[ stage ]]> <![CDATA[ EQ-Water ]]> <![CDATA[ Tin wt% ]]> preparation SBA-MP none Cl 74.5% ND Work SBA-MP Sn(II) NaOH 74.4% 11.0 preparation WBA-MP none Free base 61.6% ND Work WBA-MP Sn(II) NaOH 47.0% 18.4 preparation SBA-Gel none Cl 45.0% ND Work SBA-Gel Sn(II) NaOH 45.0% 6.7
[0087] All three anion exchange resins tested showed acceptable loading capacity for tin(II) oxide.
[0088] Example 4: Further treatment of water
[0089] As in Example 2 above, the resin was tested for absorption of chromium (VI). The resin was centrifuged and decanted to remove free water. 0.50 g of the resin was mixed with 1000 mL of the feed solution. The water was then tested for chromium content as above and reported in micrograms of chromium per gram of water. The results of the test using feed C are as follows:
[0090] 0.50g resin / feed C
[0091]
[0092] Of all three anion exchange resins tested, the tin loaded resin performed well and performed better than the same resin without tin.
[0093] Additionally, 0.50 grams of resin was tested using the above method with 1000 mL of Feed D solution. The water was tested for chromium content as above and reported in micrograms of chromium per gram of water. The results are as follows:
[0094] 0.50g resin / feed D
[0095]
[0096] Of all three anion exchange resins tested, the tin loaded resin performed well and performed better than the same resin without tin.
Claims
1. An anion exchange composition for removing hexavalent chromium from water, comprising: (a) polymer beads having covalently bonded amine groups, and (b) tin(II) oxide, in, 90 wt % or more of the tin(II) oxide, based on the total weight of the tin(II) oxide, is present inside the polymer beads, and the tin(II) oxide is not present in gaps between the polymer beads, wherein the polymer beads comprise a polymer containing polymerized units of styrene-based monomers; wherein the polymer beads comprise a polymer including polymerized units of one or more monofunctional vinyl monomers and polymerized units of one or more multifunctional vinyl monomers; wherein the volume average diameter of the polymer beads is 600 to 1,000 microns; wherein the tin(II) oxide present inside the polymer beads is in the form of particles having a diameter of less than 10 micrometers; Therein, the polymer beads contain no metal other than tin(II).
2. The composition according to claim 1, wherein The tin (II) oxide is present in an amount such that the amount of elemental tin is from 0.5 wt % to 20 wt % based on the weight of the composition.
3. The composition according to claim 1, wherein The tin(II) oxide present inside the polymer beads is in the form of particles having a diameter of 5 micrometers or less.
4. The composition according to claim 1, wherein The tin(II) oxide present inside the polymer beads is in the form of particles having a diameter of 2 micrometers or less.
5. The composition according to claim 1, wherein The tin(II) oxide present inside the polymer beads is in the form of particles having a diameter of 1 micrometer or less.
Citation Information
Patent Citations
Conditioning of ion exchangers for adsorption of oxoanions
US7708892B2
Sorbent for selective removal of contaminants from fluids
US20060237371A1
Sorbent For Selective Removal Of Contaminants From Fluids
US20080035564A1